Crystal structure reconstruction in the surface monolayer of the quantum spin liquid candidate α-RuCl3. (28th April 2020) - Dai, Zhongwei; Yu, Jie-Xiang; Zhou, Boyi; A Tenney, Samuel; Lampen-Kelley, Paula; Yan, Jiaqiang; Mandrus, David; A Henriksen, Erik; Zang, Jiadong; Pohl, Karsten; Sadowski, Jerzy T
Abstract: α -RuCl3, a layered 2D material, was recently identified as a promising candidate for realizing a Kitaev quantum spin liquid. However one fundamental property, the crystal structure, has not been well resolved yet due to difficulty of bulk diffraction techniques caused by layer stacking faults. Furthermore, the surface relaxation of monolayer-level thin films is completely unknown yet. In this report, surface sensitive low energy electron diffraction technique with µ m selectivity ( µ -LEED) combined with dynamical LEED analysis were used to reveal the detailed crystal structure of the surface monolayer of α -RuCl3 . A surface structural distortion that breaks the inversion symmetry of the ideal bulk structure was revealed. To be specific, we found the surface Cl sub-lattice is buckled with one Cl atom approximately 0.16 Å below the other two Cl atoms, in the unit cell. The Ru atomic layer shows an even larger buckling of approximately 0.31 Å. Through density functional theory (DFT) calculations, we suggested that this surface distortion may be induced by Cl-vacancies that are inevitable in this material system. Inversion symmetry breaking in this material could have a significant impact on the 2D Kitaev interaction for both, interfaces with other 2D materials, such as graphene and future monolayer devices.